Effect of Corticosteroids and Cyclophosphamide on Sex Hormone Profiles in Male Patients With Systemic Lupus Erythematosus or Systemic Sclerosis. Issue 6 (4th May 2017) - Arnaud, Laurent; Nordin, Annica; Lundholm, Hannes; Svenungsson, Elisabet; Hellbacher, Erik; Wikner, Johan; Zickert, Agneta; Gunnarsson, Iva
Abstract : Objective: Systemic lupus erythematosus (SLE) and systemic sclerosis (SSc) are autoimmune diseases that predominantly affect female patients, and therefore fewer investigations have been conducted in men. The aim of this study was to analyze sex hormone levels in male patients with SLE and those with SSc, compared to matched controls, in relation to the use of corticosteroids and cyclophosphamide (CYC). Methods: Sex hormone levels were measured in fasting blood samples from male patients with SLE (n = 71) and those with SSc (n = 29) and compared to population‐based, age‐matched male controls. Relevant hormone profiles were identified using cluster analysis. Results: Male SLE patients had higher levels of luteinizing hormone (LH) ( P < 0.0001) and more frequent bioactive testosterone deficiency ( P = 0.02) than their matched controls. The current dosage of prednisolone correlated inversely with the levels of bioactive testosterone (r = −0.36, P = 0.03). Cluster analysis identified a subset of SLE patients with increased levels of follicle‐stimulating hormone, LH, and prolactin as well as lower levels of bioactive testosterone ( P < 0.0001) in relation to higher daily doses of prednisolone. In male SSc patients, levels of testosterone ( P = 0.03) and bioactive testosterone ( P = 0.02) were significantly lower than those in matched controls. Use of CYC during the previous year was associated with lower bioactive testosterone levels in both SLE patients ( P = 0.02) and SSc patients ( P = 0.01), after adjustment for age. Conclusion: The results of this study highlight the negative impact of corticosteroids on gonadal function in men with SLE. Furthermore, use of CYC during the year prior to study inclusion impaired bioactive testosterone levels in male patients with either SLE or SSc. Physicians should be more aware of the possibility of hypogonadism in male patients with autoimmune diseases. The need for hormonal supplementation remains to be formally evaluated in these patients.